Counter-intuitive influence of Himalayan river morphodynamics on Indus Civilisation urban settlements. Issue 1 (December 2017) - Singh, Ajit; Thomsen, Kristina; Sinha, Rajiv; Buylaert, Jan-Pieter; Carter, Andrew; Mark, Darren; Mason, Philippa; Densmore, Alexander; Murray, Andrew; Jain, Mayank; Paul, Debajyoti; Gupta, Sanjeev
Abstract Urbanism in the Bronze-age Indus Civilisation (~4.6–3.9 thousand years before the present, ka) has been linked to water resources provided by large Himalayan river systems, although the largest concentrations of urban-scale Indus settlements are located far from extant Himalayan rivers. Here we analyse the sedimentary architecture, chronology and provenance of a major palaeochannel associated with many of these settlements. We show that the palaeochannel is a former course of the Sutlej River, the third largest of the present-day Himalayan rivers. Using optically stimulated luminescence dating of sand grains, we demonstrate that flow of the Sutlej in this course terminated considerably earlier than Indus occupation, with diversion to its present course complete shortly after ~8 ka. Indus urban settlements thus developed along an abandoned river valley rather than an active Himalayan river. Confinement of the Sutlej to its present incised course after ~8 ka likely reduced its propensity to re-route frequently thus enabling long-term stability for Indus settlements sited along the relict palaeochannel. The Bronze-age Indus civilisation (4.6–3.9 ka) was thought to have been linked to the development of water resources in the Himalayas. Here, the authors show that along the former course of the Sutlej River the Indus settlements developed along the abandoned river valley rather than an active Himalayan river.